The Phytomonas cell surface proteome: Insights into the evolution of the parasite-host interface in Trypanosomatids - Jaskowska, E (2018)
The trypanosomatids are a diverse group of obligate parasitic eukaryotes that have adapted to colonise multicellular and unicellular hosts that span the eukaryotic tree of life. The genetic resources that have enabled trypanosomatids to colonise such a diverse range of hosts are largely unknown. However, there is precedent that adaptation is in part facilitated through the evolution of families of cell surface proteins. The aim of this thesis was to broaden our knowledge of how trypanosomatids have adapted their cell surface to colonise different hosts through a combination of proteomic and bioinformatic approaches. The principal body of work is focussed on Phytomonas, a globally distributed genus of plant infective trypanosomatids that are transmitted by insects. As a sister group to Leishmania parasites of animals, this study of Phytomonas informs our understanding of how trypanosomatids have evolved from a monoxenous parasite of insects to adapt to both mammalian and plant hosts. To provide further resolution, a second species, Trypanosoma carassii (an extracellular parasite of cyprinid fish) was also analysed. T. carassii occupies an informative position in the phylogenetic tree of trypanosomatids as an outgroup to the salivarian and stercorarian Trypanosoma species. The results of the bioinformatic analysis presented in this thesis reveal that there is a conserved core of trypanosomatid cell surface proteins, the majority of which have no known function. Bioinformatic and proteomic results show that the cell surface of T. carassii is covered in one or more novel and unique families of GPI anchored proteins. The study of P. serpens indicates that while evolution to parasitise plants was facilitated though adaptation of the cell surface, there was no evidence for the innovation of large families of cell surface proteins as is observed in Trypanosoma and Leishmania species. Placed in an evolutionary context, the results presented in this thesis provide some insight into how these enigmatic parasites evolved from a single common ancestor to parasitise a broad host range from coconuts to crocodiles.